Characteristics of pre-cluster symptoms in cluster headache: A cross-sectional multicentre study. (June 2022) - Cho, Soohyun; Cho, Soo-Jin; Lee, Mi Ji; Park, Jeong Wook; Chu, Min Kyung; Moon, Heui-Soo; Chung, Pil-Wook; Sohn, Jong-Hee; Kim, Byung-Su; Kim, Daeyoung; Kim, Jae-Moon; Chung, Jae Myun; et al.
Background: Contrary to pre-attack symptoms before an individual cluster headache attack, little is known about the pre-cluster symptoms before the onset of cluster bouts. We previously described pre-attack symptoms before cluster headache attacks. The aim of this study was to investigate characteristics of pre-cluster symptoms in patients with episodic cluster headache. Methods: In this multicentre study, 184 patients with episodic cluster headache were recruited between October 2018 and December 2020. They were interviewed by investigators and completed a structured questionnaire. To investigate pre-cluster and pre-attack symptoms, we assessed 20 symptoms and signs using the questionnaire. Results: The upcoming cluster bout was predictable in 35.3% (n = 65/184) of the patients. When present, pre-cluster symptoms occurred at a median duration of 7 days (interquartile range, 2.3–14 days) before the onset of the cluster bout. Patients with pre-cluster symptoms showed a higher proportion of women, prevalence of pre-attack symptoms and seasonal rhythmicity, frequency of cluster headache attacks per day, and total number of cluster bouts compared to patients without pre-cluster symptoms. In univariable and multivariable logistic regression analyses, female sex was associated with the predictability of pre-cluster symptoms (odds ratio = 2.297, p  = 0.016). Conclusions: The upcoming cluster bout was predicted in approximately 35% of patients with episodic cluster headache, which may allow for an earlier preventive treatment and help understand the pathophysiology.